Schizophrenia and cancer: an epidemiological study. - Goldacre, M; Kurina, L; Wotton, C; Yeates, D; Seagroat, V (2005)
BACKGROUND: For decades there has been interest in the possibility that people with schizophrenia might have some protection against cancer, and that, if this were so, it might hold clues about aetiological mechanisms in schizophrenia. AIMS: To study cancer incidence in schizophrenia. METHOD: Cohort analysis of linked hospital and death records was used to compare cancer rates in people with schizophrenia with a reference cohort. RESULTS: We did not find a reduced risk for cancer overall (rate ratio 0.99,95% CI 0.90-1.08) or for most individual cancers. There was, however, a significantly low rate ratio for skin cancer (0.56,95% CI 0.36-0.83). CONCLUSIONS: We found no evidence that schizophrenia confers protection against cancer in general. Low rates of cancer are consistent with the hypothesis that sun exposure may influence the development of schizophrenia, although other explanations are also possible.